The Primacy of Race in the Geography of Income‐Based Voting: New Evidence from Public Voting Records. Issue 2 (13th March 2015) - Hersh, Eitan D.; Nall, Clayton
Abstract : Why does the relationship between income and partisanship vary across U.S. regions? Some answers to this question have focused on economic context (in poorer environments, economics is more salient), whereas others have focused on racial context (in racially diverse areas, richer voters oppose the party favoring redistribution). Using 73 million geocoded registration records and 185, 000 geocoded precinct returns, we examine income‐based voting across local areas. We show that the political geography of income‐based voting is inextricably tied to racial context, and only marginally explained by economic context. Within homogeneously nonblack localities, contextual income has minimal bearing on the income‐party relationship. The correlation between income and partisanship is strong in heavily black areas of the Old South and other areas with a history of racialized poverty, but weaker elsewhere, including in urbanized areas of the South. The results demonstrate that the geography of income‐based voting is inseparable from racial context.